IL-1 family cytokines and receptors in IgG4-related disease. (February 2018) - Capecchi, Riccardo; Italiani, Paola; Puxeddu, Ilaria; Pratesi, Federico; Tavoni, Antonio; Boraschi, Diana; Migliorini, Paola
Abstract: Background/aim: The IgG4-related disease (IgG4-RD) is a fibroinflammatory condition that can affect almost any organ, often associated with eosinophilia and increased levels of IgE and IgG4. Overexpression in tissues of Th2-related cytokines but also of IFN-γ has been reported. Given the major role of Il-1 family cytokines in inducing and regulating inflammation, and the paucity of data so far available in IgG-RD, we performed a comprehensive analysis of IL-18, related IL-1 family cytokines and soluble receptors in these patients. Patients and Methods: Fifteen patients fulfilling the criteria for the diagnosis of IgG4-RD and 80 blood donors as control were recruited. Cytokines of the IL-1 family (IL-1α, IL-1β, IL-33, IL-18), soluble receptors (sIL-1R1, sIL-1R2, sIL-1R3, ST2/sIL-1R4) and antagonists (IL-1Ra, IL-18 binding protein -IL-18 BP-) were measured in sera by multiarray ELISA assay. Free IL-18 was calculated as the amount of IL-18 not inhibited by IL-18 BP. Results: Half of the patients had a multiorgan disease, mainly affecting retroperitoneum, lymph nodes and pancreas. sIL-1R1 (p = 0.0001), sIL-1R2 (p = 0.0024), ST2/sIL-1R4 (p = 0.002) were significantly increased in IgG4-RD sera compared with healthy controls; sIL-R3 was significantly lower in patients vs controls (p = 0, 0006). Conclusions: The increased levels of the soluble forms of the two IL-1 receptors IL-1R1 and IL-1R2 suggest the need to dampen IL-1-mediated inflammation at the tissue level. Elevated circulating ST2/sIL-1R4 levels may represent the marker of an ongoing protective mechanism, but their contribution to organ damage cannot be excluded. On the whole, the data suggest a tight control of IL-1 family cytokines signalling in IgG4-RD.